MENGANALISIS KEUNTUNGAN DAN BIAYA TERHADAP PROSES PENGOLAHAN SARANG BURUNG WALET MENGGUNAKAN ALGORITMA C5.0 - Windania Purba; Angelin Angelin (Politeknik Bisnis Indonesia, 2021)
This study aims to analyze the costs and benefits required to produce swiftlet nests. Swallow's nest is a very popular health product today. This can happen because swallow's nest has many health benefits such as antioxidant, anti-inflammatory, antiaging, anticancer, increasing immunity and accelerating wound healing. Currently, the production of swallow's nest at PT. Cefa Indonesia Sejahtera Lestari is difficult to do so that swallow nest products are expensive. To help PT. Cefa Indonesia Sejahtera Lestari overcomes the problem of the cost of processing dirty swallow's nests to finished products so that they can be handled properly using the C5.0 algorithm by classifying these problems. The results showed that the root node was obtained, namely the drying stage of the swallow's nest. If the costs required at this stage are equivalent to the existing capital, the company will benefit. Conversely, if the required cost exceeds the existing capital, the company will experience a loss.